2011
DOI: 10.1007/s00394-011-0257-5
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 supplementation ameliorates inflammatory signaling and oxidative stress associated with strenuous exercise

Abstract: CoQ(10) supplementation before strenuous exercise decreases the oxidative stress and modulates the inflammatory signaling, reducing the subsequent muscle damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
51
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 44 publications
6
51
3
2
Order By: Relevance
“…However, after adjustment for the baseline levels, age and baseline BMI, the effect on TAC levels disappeared. Diaz-Castro et al [29] demonstrated a significant increase in the total antioxidant status (TAS) levels following the supplementation of CoQ10 before strenuous exercise among a group of amateur athletes. A significant increase in TAC levels was also observed after daily intake of 100 mg CoQ10 supplements after 12 weeks in varicocele patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, after adjustment for the baseline levels, age and baseline BMI, the effect on TAC levels disappeared. Diaz-Castro et al [29] demonstrated a significant increase in the total antioxidant status (TAS) levels following the supplementation of CoQ10 before strenuous exercise among a group of amateur athletes. A significant increase in TAC levels was also observed after daily intake of 100 mg CoQ10 supplements after 12 weeks in varicocele patients [30].…”
Section: Discussionmentioning
confidence: 99%
“…The daily intake of CoQ10 was estimated to be 3-5 mg [43]. Recent data suggests that oral supplementation of Co-enzyme Q10 during highintensity exercise reduces oxidative stress, and creatinine excretion [44]. Conversely, 8 weeks of treatment with a daily dose of 90 mg of Q10 in moderately trained subjects did not affect exercise capacity and oxidative stress [45].…”
Section: Dietary Vs Supplemental Antioxidants: Same Effectiveness?mentioning
confidence: 99%
“…However, the supplemented CG did not demonstrate increases in oxidative stress markers and witnessed a spike in catalase activity, an indication of antioxidant enhancement. 55 These results provide a rationale for further insight into the mechanism by which CoQ 10 ameliorates ROS damage.…”
Section: Exercise and Coq 10 Supplementationmentioning
confidence: 85%
“…55 Conversely, increased intensity and duration can result in episodes of fatigue and muscle injury due to ROS produced during an exercise session. As a scavenging antioxidant, it has been theorized that CoQ 10 supplementation before exercise could protect muscle cells and subsequently improve the aspects of physical performance.…”
Section: Exercise and Coq 10 Supplementationmentioning
confidence: 99%
See 1 more Smart Citation